Tracking Deaf Aesthetics in Deaf Spaces: Dramaturgical Decisions for Plays and Dance Theatre Works by Deaf-Led Teams - Weber, Joanne; Kanagasekarampillai, Thurga; Yuzwenko-Martin, Connor; Dodd, Chris; Jones, Crystal (Performance Matters, 2025)
Dramaturgy for plays featuring scripts developed with deaf actors, or by deaf playwrights, brings a layered and complex set of considerations about increasing accessibility in theatre productions for the cast, crew, and audience. These considerations include (1) making deliberate decisions about the languages the actors use; (2) addressing linguistic repertoires of the audience; (3) supporting or expanding sensory repertoires; (4) discussing the role of technology; and (5) incorporating deaf themes that are rarely known or understood by nondeaf audiences. Using a deaf aesthetics theoretical lens, the article explores dramaturgical decisions made by deaf playwrights, directors, and performers regarding four theatre and dance theatre works that were produced or are in progress in midwestern Canada between 2020 and 2025. The article also provides a performance ethnography of a staged reading for a script in progress developed by a deaf-led team of actors, a director, and a playwright. The performance ethnography relies on data collected from multiple sources: imagination-based activities resulting in artwork; steps within an adapted playbuilding model; video recordings of workshop sessions; the devised script; a video of the staged reading; and interviews with the deaf research team and participants. The data indicates that deaf aesthetics theatre practices drive accessibility strategies which are interwoven into the script.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)Dramaturgy is a way of making meaning and making people feel. People might see, hear, smell, or feel performance. So, dramaturgy is about making meaning and feeling through the senses. Dramaturgs are the people responsible for dramaturgy. When dramaturgs work on plays with deaf actors or with deaf writers they need to think about access. They must think about:The language the actors use. Will the actors speak or sign? The language the audience uses. Do they speak or sign? How many other languages do they use? How to help the audience use more than one sense. Will the play ask the audience to see as much as listen? How to use technology to increase access. How to explain the deaf experience to nondeaf audiences.This writing talks about four plays from midwestern Canada. These plays all took place in the last five years. We study a reading of a script a deaf playwright is working on with a team that is led by deaf people. We look atart made to develop the script, video of workshops, the script, video of a reading, and interviews with the deaf researchers and artists.We think about these things with deaf aesthetics theory. Deaf aesthetics theory says that deaf people should teach and make art for other deaf people. It also says art for deaf people should think about seeing and touching more than hearing. We found that deaf theatre makers don’t add access. Deaf theatre makers put access in the script from the start.